2021
DOI: 10.3390/plants10081592
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Fine-Mapping of Quantitative Trait Loci Controlling Plant Height in Central European Winter Triticale (×Triticosecale Wittmack)

Abstract: The quantitatively inherited trait plant height is routinely evaluated in triticale breeding programs as it substantially influences lodging and disease susceptibility, is a main contributor to biomass yield, and is required to improve hybrid seed production by fine-tuning plant height in the female and male parental pools in hybrid breeding programs. In this study, we evaluated a panel of 846 diverse Central European triticale genotypes to dissect the genetic architecture underlying plant height by genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Previous studies (Neuweiler et al 2020 , 2021 ; Trini et al 2021 ) have reported grain yield, thousand-kernel weight and plant height based on the same field experiment. For the other traits, the Bonferroni–Holm test was used for outlier detection (Bernal-Vasquez et al 2016 ).…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies (Neuweiler et al 2020 , 2021 ; Trini et al 2021 ) have reported grain yield, thousand-kernel weight and plant height based on the same field experiment. For the other traits, the Bonferroni–Holm test was used for outlier detection (Bernal-Vasquez et al 2016 ).…”
Section: Methodsmentioning
confidence: 96%
“…Up to now, many research studies have described the QTL regions associated with triticale resistance to both biotic and abiotic stresses such as resistance to Fusarium head blight (FHB) [ 17 , 24 , 25 , 26 ], powdery mildew [ 16 , 22 , 27 , 28 ], yellow rust [ 11 , 17 , 29 ], pink snow mold [ 30 , 31 , 32 ], drought [ 33 , 34 , 35 ], and freezing [ 23 , 32 ]. Many studies showed the analysis of QTL regions associated with the important agronomic factors and morphological features of triticale [ 36 , 37 , 38 , 39 , 40 ]. Additionally, from the breeding perspective, QTL regions linked with androgenic responsiveness [ 41 ], albino plant formation [ 42 ], and ABA accumulation in the anthers in response to stress factors [ 43 , 44 ] were also identified, which can be very useful in modifying an in vitro approach, especially in the androgenesis process.…”
Section: Qtl and Candidate Gene Analysismentioning
confidence: 99%
“…The development of semi-dwarf varieties is a reliable way to solve the lodging problem. Dwarfing genes reduce the height of the straw, increasing the yield via higher grain number per ear yield without the risk of losing it as a result of lodging [14,15]. However, in experiments with isogenic recombinant lines, the dwarfing genes, as a rule, reduce the thousand grain weight, impair the assimilation of soil nitrate nitrogen, and reduce drought resistance, and they can extend the periods of flowering and heading [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the dwarfing genes of rye, the dominant allele Ddw1 has the greatest agricultural value. The Gibberellin 2-Oxidase gene is considered a candidate for Ddw1, while its ortholog in wheat is considered to be the Rht12 gene [14,[26][27][28][29][30]. It is able to reduce the height of plants by 25-30%, but at the same time, it reduces the thousand grain weight and the weight of grains per ear [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation